The SARS-CoV Fusion Peptide Forms an Extended Bipartite Fusion Platform that Perturbs Membrane Order in a Calcium-Dependent Manner. Issue 24 (8th December 2017) - Lai, Alex L.; Millet, Jean K.; Daniel, Susan; Freed, Jack H.; Whittaker, Gary R.
Abstract: Coronaviruses (CoVs) are a major infectious disease threat and include the pathogenic human pathogens of zoonotic origin: severe acute respiratory syndrome CoV (SARS-CoV) and Middle East respiratory syndrome CoV (MERS-CoV). Entry of CoVs into host cells is mediated by the viral spike (S) protein, which is structurally categorized as a class I viral fusion protein, within the same group as influenza virus and HIV. However, S proteins have two distinct cleavage sites that can be activated by a much wider range of proteases. The exact location of the CoV fusion peptide (FP) has been disputed. However, most evidence suggests that the domain immediately downstream of the S2′ cleavage site is the FP (amino acids 798–818 SFIEDLLFNKVTLADAGFMKQY for SARS-CoV, FP1). In our previous electron spin resonance spectroscopic studies, the membrane-ordering effect of influenza virus, HIV, and Dengue virus FPs has been consistently observed. In this study, we used this effect as a criterion to identify and characterize the bona fide SARS-CoV FP. Our results indicate that both FP1 and the region immediately downstream (amino acids 816–835 KQYGECLGDINARDLICAQKF, FP2) induce significant membrane ordering. Furthermore, their effects are calcium dependent, which is consistent with in vivo data showing that calcium is required for SARS-CoV S-mediated fusion. Isothermal titration calorimetry showed a direct interaction between calcium cations and both FPs. This Ca 2 + -dependency membrane ordering was not observed with influenza FP, indicating that the CoV FP exhibits a mechanistically different behavior. Membrane-ordering effects are greater and penetrate deeper into membranes when FP1 and FP2 act in a concerted manner, suggesting that they form an extended fusion "platform." Graphical Abstract: Highlights: ESR and infectivity assays were used to study the SARS-CoV fusion peptide. Membrane-ordering ability was used as a criterion for identifying bona fide FP. FP1 (downstream of S2′ site, aa 798–818) and FP2 (aa 816–835) were identified. FP1 and FP2 act in a cooperative manner to induce greater membrane ordering. FP1- and FP2-mediated membrane fusion is calcium dependent.